2021
DOI: 10.1039/d0ra10749b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled fibrinogen–fibronectin hybrid protein nanofibers with medium-sensitive stability

Abstract: Hybrid protein nanofibers (hPNFs) have been identified as promising nano building blocks for numerous applications in nanomedicine and tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In recent years, more and more studies have been conducted on the brinogen albumin ratio (FAR). As a new biomarker for disease evaluation, FAR has been con rmed to be closely related to cancer, cardiovascular disease, sepsis and other diseases [28][29][30][31]. As a new in ammatory based prognostic parameter, FAR was founded that it more higher in non-surviving COVID-19 patients than in surviving COVID-19 patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies have been conducted on the brinogen albumin ratio (FAR). As a new biomarker for disease evaluation, FAR has been con rmed to be closely related to cancer, cardiovascular disease, sepsis and other diseases [28][29][30][31]. As a new in ammatory based prognostic parameter, FAR was founded that it more higher in non-surviving COVID-19 patients than in surviving COVID-19 patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…[18,25] Multicomponent ECM hybridization could be built on the interlay of binding domains with fibril formation. [25,30,31] On the other hand, in 2021 Neale et al demonstrated that shear-deployed FNfs could successfully induce an ordered and robust 3D network of FNfs, which can then be used to promote a directional, persistent migratory phenotype in fibroblasts. [32] Despite certain in vivo mimetic fibril structures and component hybridizations, they have yet to achieve the biologically complex structures and component configurations produced by the resident cells in a specific tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, much attention has been devoted to the design of a wide variety of self-assembling supramolecular functional structures based on naturally occurring proteins, including collagens, elastin, silk, and keratin. These structures play a central role in bottom-up nanotechnology and have the potential to be used as hydrogel scaffolds, biomimetic cellular support structures, membranes, and drug delivery vehicles. …”
Section: Introductionmentioning
confidence: 99%